The Antibacterial Activity of Leaves Ethanol Extract, Stem Bark, and Latex of Angsana (Pterocarpus indicus Willd.) towards Bacterial Growth Streptococcus mutans as in vitro - Dera Armedita; Verry Asfrizal; Masyhudi Amir (ODONTO : Dental Journal, 2018)
Background: Indonesia has many types of plants, which have medicinal properties and are used to cure various diseases. One of plant that has medicinal properties is the Angsana plant (Pterocarpus indicus Willd.) which traditionally can cure dental and oral diseases.Method: This research used experimental laboratory with disc diffusion methods. Angsana (Pterocarpus indicus Willd.) was taken from as city ornamental tree in Samarinda city. The bacteria which used were Streptococcus mutans. The samples consisted of 11 treatment groups is leaves ethanol extract, stem bark, and Angsana latex respectively with concentration 25%, 50%, 75%, positive control group (chlorhexidine 0,2%), and negative control group (sterile aquades). Data analysis using Shapiro-Wilk test and One-Way Annova test.Result: The results showed that leaves ethanol extract, stem bark, and Angsana latex (Pterocarpus indicus Willd.). All concentrations have antibacterial activity against the growth of Streptococcus mutans. The highest and the lowest concentrations that can inhibit the growth of Streptococcus mutans are 50% ethanol stem bark extract and 25% leaves ethanol extract.Conclusion: The conclusion of this study proves that the leaves, stem bark ethanol extract, and Angsana latex (Pterocarpus indicus Willd.) Have antibacterial activity against the growth of Streptococcus mutans.